ANALISA KINERJA KEUANGAN PADA PERUSAHAAN INFRASTRUKTUR TAHUN 2019 SAMPAI 2023 DI INDONESIA - Putri, Eka Noviana; Indrati, Menik (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to analyze the influence of investment decisions, capital structure, dividend policy, and inflation on a company's financial performance. This research consists of four independent ones consisting of investment decisions proxied by PER (Price Earning Ratio), capital structure proxied by DER (Debt to Equity Ratio), dividend policy proxied by DPR (Dividend Payout Ratio), and Inflation. And one dependent financial performance is proxied by ROA (Return on Assets). In this research, there were 51 companies in the infrastructure sector, but only 13 companies met the criteria. So of the 255 total observation data, only 65 data serve as sample size. The results of this research show that investment decisions have a negative effect on financial performance. Capital structure has a negative effect on financial performance. Dividend policy has a positive effect on financial performance. Inflation has a negative effect on financial performance. Overall, this research provides empirical evidence about the importance of managing investment decisions, capital structure, and dividend policy in improving company financial performance, as well as highlighting the negative impacts that must be anticipated by company management. This research can also be a consideration for investors and shareholders to be more careful in receiving financial report information provided by companies in making investment decisions in order to produce maximum returns from profits generated in financial performance reports. Keywords: Investment Decisions; Capital Structure; Dividend Policy; Inflation; Financial Performance